Strengthening concrete beams with fiberglass reinforced polymer layers (Gaceta Técnica, 2016)
Through this article the study being done at the Faculty of Engineering of Rosario, referring to the use of sheets pultruded Reinforced Polymer Fiberglass (GRP) to increase the bending strength of reinforced concrete beams is presented, THESE layers are one of the elements of compound materials most commonly used in these type of reinforcements. The material most widely distributed worldwide that constitutes it is the carbon fibers, but its high cost discourages the use in the repair of structures in the Argentine market. One of the goals of this research program is to check the possibility of replacing such sheets by fiberglass elements ofArgentinean production and significantly cheaper. The results of the tests demonstrated the feasibility of this alternative. In addition, the increased thickness of the sheets of fiberglass allows the use of additional bolted anchors, which give the system supporting capacity postcritical and ductility, much needed features, for example, for structures in seismic zone.
Keywords: pultruded plates; glass fibers; flexural strengthening